Experiments on an ice ball impacting onto a rigid target - Chen, Siyu; Gad, Emad; Zhang, Lihai; Lam, Nelson; Xu, Shanqing; Lu, Guoxing (International journal of impact engineering, 2022)
•The ice ball impact onto a rigid target is extensively investigated in experiments.•Empirical relations are proposed to predict the impact response of ice balls.•The relations can accurately predict the experimental results conducted by others.•The impulse in the impact is equal to the input momentum of ice balls. This paper is concerned with the peak force (Fp) and time of occurrence (Tp) generated by the spherical ice specimen impacting onto a rigid target. The ice specimens had diameter ranging from 31.8 to 50.8 mm, and were prepared at temperature of -10°C and -30°C, respectively. The key original contribution of the article is the derivation of a correlation relationship for providing accurate predictions of Fp and Tp, for given hail size, velocity and temperature. A total of 149 Hopkinson bar tests were conducted, with impact velocity varying from 13 to 105 m/s for measuring the impact force. The tensile strength of ice, which is a term in the predictive expressions (and is measurable by the Brazilian tests), can be adjusted to take into account changes in temperature of the ice specimen. Experimental results showed that as the size of the ice specimen and its impact velocity increases, Fp increases significantly whereas Tp only increases slightly. Lowering of the temperature resulted in an increase in Fp, and decrease in Tp. Dimensional analysis was employed for processing the experimental data. Empirical relationships expressed as functions of impact velocity, specimen radius, tensile strength of ice, ice density and elastic wave speed of ice were derived. The ratio of the measured impulse to the momentum generated by the impact has also been checked, and was found to be within the range of 0.8 to 1.12. The derived empirical relationships will serve as a guide for further investigations into the structural responses to impact of an ice ball. [Display omitted]